2009
DOI: 10.1163/157075609x437682
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic administration of ghrelin on rat sperm quality and membrane integrity

Abstract: Although ghrelin acts as a modulator of feeding behavior and energy metabolism in the central nervous system, recent studies have implicated the peripheral actions of ghrelin in reproductive tissues. Here, we investigated the eff ects of chronic administration of ghrelin on the motility, plasma membrane integrity and concentration of rat spermatozoa. 45-d male Wistar rats were scheduled for the study and were divided into control and treatment groups. In the treatment group, 1 nmol of ghrelin was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recently, antioxidant properties of ghrelin have been demonstrated in our laboratory in the rat testis (Kheradmand et al ., ) and ovary (Kheradmand et al ., ) so that ghrelin was able to promote antioxidant enzyme activities (especially GPx) and reduce lipid peroxidation in the testis. In addition, we indicated that chronic administration of ghrelin increases functional membrane integrity of rat spermatozoa (Kheradmand et al ., ). Likewise, the antioxidant properties of ghrelin are in consistent with our another study, in which we have shown that ghrelin enhances viability of rat spermatozoa during incubation at 37 °C up to 5 h, because of its antioxidant characteristics (Kheradmand et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, antioxidant properties of ghrelin have been demonstrated in our laboratory in the rat testis (Kheradmand et al ., ) and ovary (Kheradmand et al ., ) so that ghrelin was able to promote antioxidant enzyme activities (especially GPx) and reduce lipid peroxidation in the testis. In addition, we indicated that chronic administration of ghrelin increases functional membrane integrity of rat spermatozoa (Kheradmand et al ., ). Likewise, the antioxidant properties of ghrelin are in consistent with our another study, in which we have shown that ghrelin enhances viability of rat spermatozoa during incubation at 37 °C up to 5 h, because of its antioxidant characteristics (Kheradmand et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Considering that epididymal spermatozoa are not protected by the microenvironment provided by the sertoli cell barrier, and plasma membrane of spermatozoa are rich in high level of polyunsaturated fatty acids [27], protection of spermatozoa against oxidative stress has a remarkable importance. It has been revealed that chronic injection of ghrelin (as a new antioxidant agent) significantly increases functional plasma membrane integrity in rat spermatozoa [13].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, expression of GHS-R 1a in the seminiferous tubules strongly suggests that the seminiferous epithelium might be a target for ghrelin action and directly regulates seminiferous tubule functions [13]. Thus, it is expectable that injection of ghrelin may alter the number and/or proliferative rate of testicular cells.…”
Section: Discussionmentioning
confidence: 99%